(untitled) - Phan, Thanh Nhàn (Hà Nội, 2014)
Quyển sách diễn giải từng địa danh ở Kiên Giang rất cụ thể.
Keywords: Names, geographical,Tên địa lý; Description and travel,Mô tả và du hành; Vietnam,Việt Nam